Self-Efficacy Among Indonesian Chronic Liver Disease Patients - Siburian, Apriliani; Chang, Ching Fen (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Chronic Liver Diseases are among the most extensive diseases globally and are related to significant morbidity and mortality. Although physical well-being has long been the primary goal of medical care, as chronic disease becomes more prevalent in developed countries, there has been a greater focus on patients' emotional and social well-being. This study aimed to describe the self-efficacy among chronic liver disease patients in North Sumatra, Indonesia. This study uses a cross-sectional design. The study assessed 102 chronic liver disease patients from two hospitals using the Chronic Disease Self-Efficacy Scales Indonesian version. The participants had moderate self-efficacy (58.8%), followed by high self-efficacy (38.2%). The majority of the patients in this study had moderate self-efficacy because many individuals with chronic liver disease suffer chronic fatigue, abdominal pain and swelling, itchy skin, nausea or vomiting, loss of appetite, and other symptoms that affect self-efficacy. Health professionals should strengthen patients' self-efficacy by engaging in positive activities and enhancing their coping skills